Method for preparing hollow annular carbon nitride by using annular microreactor
The preparation of hollow ring carbon nitride through ring microreactor and microfluidic control technology has solved the environmental pollution problems of silicon-based material etching and soft template method, and achieved efficient photocatalytic performance and low pollution process, reducing equipment corrosion and pollution.
Patent Information
- Application Number
- CN202411350673.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, when preparing photocatalysts, harmful substances will be introduced during the etching of commonly used silicon-based materials, and the soft template method requires complex post-processing to remove the template, resulting in environmental pollution and equipment corrosion.
The ring microreactor is used to prepare spherical silica through microfluidic control technology. After carbon nitride is loaded, the microchannel process is de-templated, and the photocatalytic performance is enhanced through molten salt calcination, which shortens the de-template time and reagent dosage, and reduces the environment. Pollution and equipment corrosion.
The prepared hollow annular carbon nitride has a higher specific surface area and a wider light absorption range, reducing environmental pollution and equipment corrosion, and the photocatalytic system is not prone to pollution and safety hazards.
Smart Images

Figure CN119284846A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal mine fully mechanized mining, in particular to a method for preparing hollow annular carbon nitride by utilizing an annular microreactor. Background Art
[0002] It is particularly important to establish and improve a green, low-carbon, circular development system and improve the energy structure. Energy and environment are two important aspects of sustainable development for human society. Solar energy plays a huge role. In particular, the photocatalytic conversion is achieved through abundant and sustainable biomass and inexhaustible solar energy as the only energy input, which effectively promotes carbon recycling, not only reduces CO2 emissions, but also helps to alleviate the energy crisis.
[0003] The performance of photocatalytic oxidation depends on two major factors: the physical and chemical properties of the catalyst (specific surface area, pore structure, distribution of active sites, etc.) and the photoelectrochemical properties (visible light absorption capacity, photogenerated charge separation and transport performance). Researchers hope to prepare photocatalysts with advantages such as high specific surface area, high stability, ability to inhibit electron-hole recombination, and ability to utilize visible light by modifying semiconductor materials. Common modification methods include heterostructure construction, atomic doping, morphology regulation, and precious metal deposition. Based on the fact that the bulk structure of pure g-C3N4 has a very small specific surface area and lacks reactive active sites, it is not conducive to the improvement of photocatalytic activity. People have prepared g-C3N4 with different morphologies of 0D / 1D / 2D / 3D by morphology regulation. Due to the polymerization characteristics of g-C3N4, it has a flexible structure, and a variety of different characteristic morphologies can be obtained through hard template method, soft template method and self-template method, including nano, nanotube, porous structure and hollow sphere, etc., which can effectively increase the specific surface area and promote charge separation and diffusion.
[0004] However, the use of conventional silicon-based materials will introduce a large amount of HF or NH4HF2 that is harmful to the environment for etching, and the use of conventional surfactants as soft templates requires complex post-processing to remove the template. In order to overcome these problems, this patent provides a method for preparing hollow annular carbon nitride using a ring microreactor. It uses microfluidic technology to prepare spherical silicon dioxide, and then after the carbon nitride is successfully loaded, it continues to be de-templated using microfluidic technology, and finally its photocatalytic performance is enhanced by molten salt calcination. Among them, the microchannel process can shorten the time and reagent dosage of de-templating, greatly reducing environmental pollution and corrosion to equipment. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above and / or existing problems in the method for preparing hollow annular carbon nitride using an annular microreactor, the present invention is proposed.
[0007] Therefore, the problem to be solved by the present invention is how to provide a method for preparing hollow annular carbon nitride using an annular microreactor.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing hollow annular carbon nitride using an annular microreactor, comprising: configuring water, ethanol, and ammonia water as phase A, and TEOS and ethanol as phase B in proportion, pumping them into the annular microreactor at a fixed flow rate using a syringe pump and then taking them out, washing them with water and ethanol respectively, centrifuging them, and drying and grinding them to obtain silicon dioxide powder;
[0009] The spherical silicon dioxide and the carbon nitride precursor mixture are mixed in proportion, ground evenly, and then calcined, and then taken out and ground to obtain carbon nitride-loaded silicon dioxide powder;
[0010] Carbon nitride loaded with silicon dioxide powder is added to a certain amount of water as phase C, and pumped into a ring microreactor with a hydrofluoric acid solution as phase D, reacted for a certain time, washed with water and alcohol, and then centrifuged to obtain a hollow ring-shaped carbon nitride.
[0011] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, when preparing the phase A solution, the volume ratio of water, ethanol and ammonia water is 1:(5-10):(2-4), and in the phase B solution, the volume ratio of TEOS and ethanol is 1:(3-10).
[0012] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the flow rate of pumping the phase A solution into the annular microreactor is 0.05-0.1 mL / min, and the flow rate of pumping the phase B solution into the annular microreactor is 0.15-0.3 mL / min.
[0013] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the carbon nitride precursor mixture includes a mixture of urea, thiourea and cyanamide, and the cyanamide mixture is a mixture of any two or three of melamine, dicyandiamide and monocyanamide.
[0014] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the concentration of carbon nitride loaded with silicon dioxide in the C phase solution is 1-5 g / L, and the concentration of hydrofluoric acid is 5-30 g / L.
[0015] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the flow rate of pumping the C phase solution into the annular microreactor is 0.01-0.05 mL / min, and the flow rate of pumping the D phase solution into the annular microreactor is 0.01-0.1 mL / min.
[0016] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the molten salt calcination procedure is to maintain the temperature at 300°C for 1 hour, at 400°C for 1 hour, and at 500°C for 2 hours.
[0017] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, the annular microreactor comprises an annular quartz microchannel reactor, an inlet and an outlet, and the inlet and the outlet are placed on one side.
[0018] As a preferred embodiment of the method for preparing hollow annular carbon nitride by using an annular microreactor according to the present invention, the photoreaction device comprises a reaction container, an oxygen bottle, a filter and a light source.
[0019] As a preferred embodiment of the method for preparing hollow annular carbon nitride using an annular microreactor according to the present invention, after obtaining the hollow annular carbon nitride, the hollow annular carbon nitride is mixed with sodium chloride and potassium chloride in proportion and calcined continuously to obtain a molten salt carbon nitride sample.
[0020] The beneficial effects of the present invention are as follows: the photocatalytic hollow ring carbon nitride in the reaction system of the present invention is obtained by a silicon dioxide template method, and compared with bulk carbon nitride, its hollow ring morphology has a higher specific surface area, a smaller band gap, and a wider light absorption range;
[0021] The microchannel process of the present invention can shorten the template preparation time, reduce the template removal time and reagent dosage, and greatly reduce environmental pollution and corrosion to equipment;
[0022] The reaction system of the present invention adopts a photocatalytic system, which uses a photocatalyst to react with water and oxygen, is not likely to cause environmental pollution and operational safety hazards, and has fewer process steps for preparing hydrogen peroxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 The figure is a schematic diagram of the process flow of the micro-reaction device used in the present invention.
[0025] Figure 2 TEM image of spherical silica in Example 2.
[0026] Figure 3 This is the TEM image of bulk carbon nitride in Comparative Example 2.
[0027] Figure 4 This is the TEM image of the hollow spherical carbon nitride in Example 5.
[0028] Figure 5 This is an IR comparison chart of the blocky carbon nitride in Comparative Example 1 and the hollow spherical carbon nitride in Example 5.
[0029] Figure 6 This is an XPS comparison chart of the bulk carbon nitride in Comparative Example 1 and the hollow spherical carbon nitride in Example 5.
[0030] Figure 7 This is a comparison chart of the XRD of the bulk carbon nitride in Comparative Example 1 and the hollow spherical carbon nitride in Example 5. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] Example 1
[0035] Reference Figure 1, which is the first embodiment of the present invention, provides a method for preparing hollow annular carbon nitride using an annular microreactor, which comprises the following steps:
[0036] S1, water, ethanol, and ammonia water are prepared in proportion as phase A, and TEOS and ethanol are prepared as phase B, and the mixture is pumped into the ring microreactor at a fixed flow rate by a syringe pump, and then taken out, washed with water and ethanol respectively, and then centrifuged, and dried and ground to obtain silicon dioxide powder;
[0037] S2, mixing the spherical silicon dioxide and the carbon nitride precursor mixture in proportion, grinding them evenly and then calcining them, taking them out and grinding them to obtain carbon nitride-loaded silicon dioxide powder;
[0038] S3, adding carbon nitride loaded silicon dioxide powder into a certain amount of water as phase C, and pumping it into a ring microreactor with a hydrofluoric acid solution as phase D, reacting for a certain time, washing with water and alcohol, and then centrifuging to obtain a hollow ring-shaped carbon nitride.
[0039] Furthermore, when preparing the phase A solution, the volume ratio of water, ethanol and ammonia water is 1:(5-10):(2-4), and in the phase B solution, the volume ratio of TEOS and ethanol is 1:(3-10). The flow rate of pumping the phase A solution into the ring-type microreactor is 0.05-0.1 mL / min, the flow rate of pumping the phase B solution into the ring-type microreactor is 0.15-0.3 mL / min, the flow rate of pumping the phase C solution into the ring-type microreactor is 0.01-0.05 mL / min, and the flow rate of pumping the phase D solution into the ring-type microreactor is 0.01-0.1 mL / min.
[0040] Preferably, the carbon nitride precursor mixture includes a mixture of urea, thiourea and cyanamide, the cyanamide mixture is a mixture of any two or three of melamine, dicyandiamide and monocyanamide, and the molten salt calcination procedure is 300°C for 1 hour, 400°C for 1 hour, and 500°C for 2 hours.
[0041] In this embodiment, the annular microreactor includes an annular quartz microchannel reactor, an inlet, and an outlet, wherein the inlet and the outlet are placed on one side, and the photoreaction device includes a reaction container, an oxygen cylinder, a filter, and a light source.
[0042] Preferably, after obtaining the hollow ring-shaped carbon nitride, the hollow ring-shaped carbon nitride is mixed with sodium chloride and potassium chloride in proportion and further calcined to obtain a molten salt carbon nitride sample. The hollow ring-shaped sample is further calcined with the molten salt to further improve the photocatalytic performance.
[0043] In the C phase solution, the concentration of carbon nitride loaded silicon dioxide is 1-5 g / L, and the concentration of hydrofluoric acid is 5-30 g / L.
[0044] Example 2 (Preparation and Application of Spherical Silica Template):
[0045] (1) Weighing 1 mL of water, 7 mL of ethanol, and 4 mL of ammonia water as phase A, and 2 mL of TEOS and 10 mL of ethanol as phase B, and pumping them into the ring microreactor at a set flow rate using a syringe pump, and then taking them out, the flow rate of solution A is 0.1 mL / min, and the flow rate of solution B is 0.3 mL / min, washing with water and ethanol respectively, and then centrifuging to obtain a solid, and drying and grinding to obtain a white spherical silica powder;
[0046] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 0.053 mmol / g. -1 h -1 ;
[0047] Among them, the photoreaction process of the catalyst and the product concentration detection method are:
[0048] (1) Photoreaction process: 0.5 mL of isopropanol was weighed and added to 10 mL of aqueous solution containing 10 mg of catalyst, 1 mol / L HCl solution was added to adjust the pH to 3-4, and then oxygen was introduced. The reaction time was 60 min and the reaction temperature was 25°C.
[0049] Hydrogen peroxide concentration detection: Weigh about 0.1g of potassium titanium oxalate reagent with a weighing instrument and add it to a preheated 10mL volumetric flask. Add 2mL of concentrated sulfuric acid and stir quickly to evenly, then dilute to the scale with distilled water. Take 5mL of hydrogen peroxide standard solution and add it to another 10mL volumetric flask. Place the two bottles in a spectrophotometer and set the wavelength to 410nm. Record the absorbance value of the potassium titanium oxalate reagent solution (A1) and the absorbance value of the standard solution containing hydrogen peroxide (A2). Calculate the concentration of hydrogen peroxide using the following formula: [H2O2] = (A2-A1) / slope, where the slope is the slope of the hydrogen peroxide standard curve.
[0050] Example 3 (Preparation and application of spherical silica template):
[0051] (1) Weighing 1 mL of water, 5 mL of ethanol, and 2 mL of ammonia water as phase A, and 2 mL of TEOS and 6 mL of ethanol as phase B, and pumping them into the ring microreactor at a set flow rate using a syringe pump, and then taking them out, the flow rate of solution A is 0.1 mL / min, and the flow rate of solution B is 0.3 mL / min, washing with water and ethanol respectively, and then centrifuging to obtain a solid, and drying and grinding to obtain a white spherical silica powder;
[0052] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 0.039 mmol / g -1 h -1 ;
[0053] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0054] Example 4 (Preparation and Application of Carbon Nitride-Loaded Silica):
[0055] (1) Spherical silicon dioxide (Example 1) and carbon nitride precursor (urea, melamine) were mixed in a mass ratio of 8:3:1, ground evenly and placed in a muffle furnace for calcination. The calcination procedure was 350°C for 1 hour, 450°C for 1 hour, and 550°C for 4 hours. After a certain period of time, the mixture was taken out and ground to obtain yellow carbon nitride-loaded silicon dioxide powder;
[0056] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 0.410 mmol / g. -1 h -1 ;
[0057] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0058] Example 5 (Preparation and Application of Carbon Nitride-Loaded Silica):
[0059] (1) Spherical silicon dioxide (Example 1) and carbon nitride precursor (urea, melamine) were mixed in a mass ratio of 12:3:1, ground evenly and placed in a muffle furnace for calcination. The calcination procedure was 350°C for 1 hour, 450°C for 1 hour, and 550°C for 4 hours. After a certain period of time, the mixture was taken out and ground to obtain yellow carbon nitride-loaded silicon dioxide powder;
[0060] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 0.731 mmol / g. -1 h -1 ;
[0061] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0062] Example 6 (Preparation and Application of Hollow Spherical Carbon Nitride):
[0063] (1) 1 g of carbon nitride-supported silica powder (Example 4) was added to 1 L of water as phase C, and pumped into a ring microreactor with 10 g / L hydrofluoric acid solution as phase D, with the flow rate of solution A being 0.05 mL / min and the flow rate of solution B being 0.15 mL / min. After staying for 15 min, the mixture was taken out, washed with water and alcohol, and then centrifuged to obtain a beige hollow ring-shaped carbon nitride.
[0064] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 1.10 mmol / g -1 h -1 ;
[0065] The molten salt calcination procedure is to maintain the temperature at 300°C for 1 hour, 400°C for 1 hour, and 500°C for 2 hours.
[0066] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0067] Example 7 (Preparation and Application of Hollow Spherical Carbon Nitride):
[0068] (1) 1 g of carbon nitride-supported silica powder (Example 4) was added to 1 L of water as phase C, and pumped into a ring microreactor with 20 g / L hydrofluoric acid solution as phase D, with the flow rate of solution A being 0.05 mL / min and the flow rate of solution B being 0.15 mL / min. After staying for 15 min, the mixture was taken out, washed with water and alcohol, and then centrifuged to obtain a beige hollow ring-shaped carbon nitride.
[0069] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 1.33 mmol / g. -1 h -1 ;
[0070] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0071] Example 8 (Preparation and Application of Hollow Spherical Carbon Nitride):
[0072] (1) 1 g of carbon nitride-supported silica powder (Example 4) was added to 1 L of water as phase C, and pumped into a ring microreactor with 20 g / L hydrofluoric acid solution as phase D, with the flow rate of solution A being 0.025 mL / min and the flow rate of solution B being 0.075 mL / min. After staying for 30 min, the mixture was taken out, washed with water and alcohol, and then centrifuged to obtain a beige hollow ring-shaped carbon nitride.
[0073] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 1.69 mmol / g. -1 h -1 ;
[0074] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0075] Example 9 (Preparation and Application of Molten Salt Hollow Spherical Carbon Nitride):
[0076] (1) Mix the hollow spherical carbon nitride (Example 7) and metal chloride (potassium chloride, sodium chloride) in a mass ratio of 1:2.5:1, grind them evenly and put them into a muffle furnace for calcination. The calcination procedure is 300°C for 1 hour, 400°C for 1 hour, and 500°C for 2 hours. After cooling, take them out and grind them to obtain molten salt hollow spherical carbon nitride powder;
[0077] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 2.27 mmol / g. -1 h -1 ;
[0078] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0079] Example 10 (Preparation and Application of Molten Salt Hollow Spherical Carbon Nitride):
[0080] (1) Mix the hollow spherical carbon nitride (Example 7) and metal chloride (potassium chloride, lithium chloride) in a mass ratio of 1:2.5:1, grind them evenly and put them into a muffle furnace for calcination. The calcination procedure is 300°C for 1 hour, 400°C for 1 hour, and 500°C for 2 hours. After cooling, take them out and grind them to obtain molten salt hollow spherical carbon nitride powder;
[0081] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 2.05 mmol / g. -1 h -1 ;
[0082] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0083] Comparative Example 1 (Preparation and Application of Bulk Carbon Nitride):
[0084] (1) Mix the carbon nitride precursors (urea and melamine) in a mass ratio of 3:1, grind them evenly, and put them into a muffle furnace for calcination. The calcination procedure is 350°C for 1 hour, 450°C for 1 hour, and 550°C for 4 hours. After cooling, take them out and grind them to obtain blocky carbon nitride powder;
[0085] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 0.132 mmol / g -1 h -1 ;
[0086] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0087] Comparative Example 2 (Preparation and Application of Molten Salt Block Carbon Nitride):
[0088] (1) Mix bulk carbon nitride (Comparative Example 1) and metal chloride (potassium chloride, lithium chloride) in a mass ratio of 1:2.5:1, grind them evenly and put them into a muffle furnace for calcination. The calcination procedure is 300°C for 1 hour, 400°C for 1 hour, and 500°C for 2 hours. After cooling, take them out and grind them to obtain molten salt bulk carbon nitride powder;
[0089] (2) Weigh 0.5 mL of isopropanol and add it to 10 mL of aqueous solution containing 10 mg of catalyst. Add 1 mol / L HCl solution to adjust the pH to 3-4, then introduce oxygen. After the photoreaction for 1 hour, the concentration of hydrogen peroxide is measured to be 1.025 mmol / g -1 h -1 ;
[0090] The photoreaction process of the catalyst and the method for detecting the product concentration are the same as those in Example 2 and will not be described in detail here.
[0091] The experimental results show that the use of photocatalysts to react with water and oxygen is not likely to cause environmental pollution and operational safety hazards, and the process steps for preparing hydrogen peroxide are relatively few. The photocatalytic hollow ring carbon nitride in the reaction system of the present invention is obtained by the silicon dioxide template method. Compared with bulk carbon nitride, its hollow ring morphology has a higher specific surface area, a smaller band gap, and a wider light absorption range. The microchannel process in the present invention can shorten the template preparation time, while reducing the time and reagent dosage for de-templating, greatly reducing environmental pollution and corrosion to equipment.
[0092] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing hollow annular carbon nitride using an annular microreactor, characterized in that: include, Water, ethanol, and ammonia water are prepared in proportion as phase A, and TEOS and ethanol are prepared as phase B, and the mixture is pumped into the ring microreactor at a fixed flow rate by a syringe pump, and then taken out, washed with water and ethanol respectively, centrifuged, and dried and ground to obtain silicon dioxide powder; The spherical silicon dioxide and the carbon nitride precursor mixture are mixed in proportion, ground evenly, and then calcined, and then taken out and ground to obtain carbon nitride-loaded silicon dioxide powder; Carbon nitride loaded with silicon dioxide powder is added to a certain amount of water as phase C, and pumped into a ring microreactor with a hydrofluoric acid solution as phase D, reacted for a certain time, washed with water and alcohol, and then centrifuged to obtain a hollow ring-shaped carbon nitride.
2. The method for preparing hollow annular carbon nitride using an annular microreactor according to claim 1, characterized in that: When preparing the phase A solution, the volume ratio of water, ethanol and ammonia water is 1:(5-10):(2-4), and in the phase B solution, the volume ratio of TEOS and ethanol is 1:(3-10).
3. The method for preparing hollow annular carbon nitride using an annular microreactor according to claim 1 or 2, characterized in that: The flow rate of pumping the phase A solution into the ring microreactor is 0.05-0.1 mL / min, and the flow rate of pumping the phase B solution into the ring microreactor is 0.15-0.3 mL / min.
4. The method for preparing hollow annular carbon nitride using an annular microreactor as claimed in claim 3, characterized in that: The carbon nitride precursor mixture includes a mixture of urea, thiourea and cyanamide, and the cyanamide mixture is a mixture of any two or three of melamine, dicyandiamide and monocyanamide.
5. The method for preparing hollow annular carbon nitride using an annular microreactor according to any one of claims 1, 2 and 4, characterized in that: In the C phase solution, the concentration of carbon nitride loaded silicon dioxide is 1-5 g / L, and the concentration of hydrofluoric acid is 5-30 g / L.
6. The method for preparing hollow annular carbon nitride using an annular microreactor as claimed in claim 5, characterized in that: The flow rate of pumping the phase C solution into the ring microreactor is 0.01-0.05 mL / min, and the flow rate of pumping the phase D solution into the ring microreactor is 0.01-0.1 mL / min.
7. The method for preparing hollow annular carbon nitride using an annular microreactor as claimed in claim 6, characterized in that: The molten salt calcination procedure is to maintain at 300° C. for 1 hour, maintain at 400° C. for 1 hour, and maintain at 500° C. for 2 hours.
8. The method for preparing hollow annular carbon nitride using an annular microreactor according to claim 6 or 7, characterized in that: The annular microreactor comprises an annular quartz microchannel reactor, an inlet and an outlet, wherein the inlet and the outlet are placed on one side.
9. The method for preparing hollow annular carbon nitride using an annular microreactor as claimed in claim 8, characterized in that: The photoreaction device includes a reaction container, an oxygen bottle, a filter and a light source.
10. The method for preparing hollow annular carbon nitride using an annular microreactor according to claim 8, characterized in that: After the hollow ring-shaped carbon nitride is obtained, the hollow ring-shaped carbon nitride is mixed with sodium chloride and potassium chloride in proportion and calcined continuously to obtain a molten salt carbon nitride sample.